Ecosystem Learning with Sparkol Videoscribe-Based Learning Media - Widiari, Luh Eka Ratna; Astawan, I Gede (International Journal of Elementary Education, 2021)
This research is based on the low learning outcomes caused by the lack of use of creative and innovative learning media. This study aims to create a media building design and produce learning media products based on sparkol videoscribe on the topic of the fifth grade elementary school ecosystem that has been tested for its validity. This development research uses a 4D research model. The subjects of this development research trial were 2 subject content expert lecturers, 2 instructional design expert lecturers, 2 media expert lecturers, and 1 grade V teacher and 9 students. The data collection method used in this development research is a questionnaire method in the form of a four-scale rating scale instrument given to the test subjects. The average score of subject content experts is 3.81 with very good qualifications, the average score of learning design experts is 3.68 with very good qualifications and the average score of learning media experts is 3.79 with qualifications very good. Then from the results of the teacher assessment obtained an overall average of 3.90 with very good qualifications. Data on the results of individual trials obtained an average of 3.89 with very good qualifications and data from small group trials obtained an average of 3.94 with very good qualifications. Based on the results of the analysis of the validity test by experts and teachers, learning media based on sparkol videoscribe on the topic of the fifth grade elementary school ecosystem is declared valid and suitable for use in learning.